A Modern Annuity for Canada — Concrete Reconciliation - Mason, Gregory; Jones, Sheilla; Helgason, Wayne (Journal of Aboriginal Economic Development, 2020)
Canada's history features many commercial compacts, agreements, and treaties marking the evolution of the relations between Indigenous Peoples and Settlers. The treaties negotiated between 1850 and 1921 comprised three main elements: the allocation of land for the exclusive use of the signatory First Nations; preservation of hunting and fishing rights; and an individual annuity paid to each band member, plus a one-time payment made to the band. The individual annuity was minimal, even in the later 19th century, and has remained unchanged since 1878. This paper explores the rationale, design, implementation, and cost of a Modern Annuity as the concrete measure for reconciliation, acknowledging the value of the land ceded to Canada by the Indigenous peoples.